PENGARUH PENILAIAN PRESTASI KERJA, KETERAMPILAN, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA GURU (Studi Kasus Pada SMK Kesehatan Letris Indonesia 2 Tangerang Selatan): Fakultas Ekonomi dan Bisnis, Universitas Budi Luhur Jakarta - Salsabila, Zaliza; Wahyudi, Widi (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2024)
This study aims to determine the impact of work performance appraisals, skills, and leadership styles on teacher performance at SMK Kesehatan Letris Indonesia 2. The study adopts a quantitative research design with a population consisting of all teachers at SMK Kesehatan Letris Indonesia 2, totaling 38 individuals. Data collection was carried out through a questionnaire, and data analysis was conducted using Microsoft Excel 2019 and SPSS version 20. Given the relatively small population size, the study opted to include the entire population as the sample (saturated sampling). This technique allows for the generalization of research results to the entire population of teachers at the school. Multiple linear regression analysis resulted in a model that can be used to predict the value of Y based on the values of X1, X2, and X3, with the equation Y = 4.004 + 0.517X1 + 0.741X2 + 0.020X3. The findings of this study conclude that enhancing work performance appraisals and developing teacher skills can be effective strategies for improving overall teacher performance. Conversely, improvements in leadership style in the context of this study did not prove to contribute significantly to enhancing teacher performance.